Usability Assessments for Augmented Reality Motor Rehabilitation Solutions: A Systematic Review. (1st November 2018) - Cavalcanti, Virgínia C.; Santana, Maria I. de; Gama, Alana E. F. Da; Correia, Walter F. M.
Abstract : This article aims to understand which methods and user assessment approaches are most commonly used in motor rehabilitation studies that use Augmented Reality (AR) applications. The way in which this was performed and discussed was through a systematic review of the area. Firstly, the different uses of AR in these treatments, and the importance of improving usability studies to evaluate these interfaces and their interactions with their users, were discussed. Then, the systematic review of the literature was structured according to previous studies and covered the period from 2007 to September 2017, using the main scientific journals of the area. Of the 666 results collected in the initial search, 32 articles were selected within the planned requirements and scope. These publications were classified by relevance, using the QualSyst evaluation tool for health technology research, and the type of evaluation, approach, and methods used were catalogued. It was found that most of the studies prioritise methods of data collection, such as task execution and performance analysis. However, through QualSyst, it was verified that the best-evaluated studies chose to use a combination of quantitative and qualitative analysis, through the application of methods such as user preference questionnaires, interviews, and observations. The results presented in this review may benefit designers who intend to design and conduct usability assessments for AR within this context.